E-voting jako forma demokracji bezpośredniej. Dotychczasowe doświadczenia i ich konsekwencje - Duda, Krzysztof (Wydawnictwo Naukowe WNPiD UAM, Poznań, 2011)
This article is going to Point main advantages and disadvantages of e-voting. That form of voting could be a turning point in modern democracy. It can avoid many concerns and problems – there are some certain examples attached. It’s our choice to try e-votig but it’ is essential to know all pros and cons.
E-voting as a Form of Direct Democracy. Some Experiments and Their Consequences
Keywords: e-voting; wybory; referendum; e-demokracja